An enhanced scheme to support QoS in MIPv6 based networks using DiffServ - Ibrahim, Loay; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Khalifa, Othman Omran; Mahmoud, Omer; Hameed, Shihab A.; Daoud, Jamal Ibrahim (INSI Publications, 2011)
Quality of Service (QoS) is the ability of network elements (e.g. application, host and router) to provide some level of assurance for consistent network data delivery. Within a few past decades, QoS is certainly not supported over the IP-based networks. The Internet Protocol offers BestEffort services to its applications, i.e. there is no QoS commitment offered. Obviously, in this service, the network makes its best attempt to deliver the packets to their destinations but with no guarantees and no special resources allocated for any of the packets. The forwarding of packets is completely equal. That means all packets receive the same Quality of Service. The same case scenario happens with the standard MIPv6 except that it was designed to allow nodes to be reachable and maintain ongoing connections while changing their location within the topology. The Best-Effort service works fine with the conventional Internet applications (non real-time applications) such as remote login, electronic mail and file transfer. In contrary, real-time applications like video telephony and virtual conferencing require QoS guarantee in lieu of the Best-Effort delivery. As a result, Internet Engineering Task Force (IETF) has proposed three major models to support QoS in the Internet namely, IntServ, DiffServ and MPLS. Unfortunately, these QoS models were initially designed without mobility in-mind. Hence, they are not fully adapted to mobile environments yet. Integrating QoS with mobility support seems to be needed to fulfill the necessity of users. This paper aims to propose an efficient scheme to enhance QoS in the mobile IPv6 networks. The proposed scheme (DiffServMIPv6) was evaluated using the analytical analysis approach in order to generate the signaling cost. The signaling cost has been investigated to assess the performance of the proposed scheme compared to the standard Mobile IPv6 which was proposed by IETF.